Common and separable neural alterations in adult and adolescent depression – Evidence from neuroimaging meta-analyses - Bore, Mercy Chepngetich; Liu, Xiqin; Huang, Xiaoqi; Kendrick, Keith M.; Zhou, Bo; Zhang, Jie; Klugah-Brown, Benjamin; Becker, Benjamin (Neuroscience and biobehavioral reviews, 2024)
Depression is a highly prevalent and debilitating mental disorder that often begins in adolescence. However, it remains unclear whether adults and adolescents with depression exhibit common or distinct brain dysfunctions during reward processing. We aimed to identify common and separable neurofunctional alterations during receipt of rewards and brain structure in adolescents and adults with depression. A coordinate-based meta-analysis was employed using Seed-based d mapping with permutation of subject images (SDM-PSI). Compared with healthy controls, both age groups exhibited common activity decreases in the right striatum (putamen, caudate) and subgenual ACC. Adults with depression showed decreased reactivity in the right putamen and subgenual ACC, while adolescents with depression showed decreased activity in the left mid cingulate, right caudate but increased reactivity in the right postcentral gyrus. This meta-analysis revealed shared (caudate) and separable (putamen and mid cingulate cortex) reward-related alterations in adults and adolescents with depression. The findings suggest age-specific neurofunctional alterations and stress the importance of adolescent-specific interventions that target social functions. •Reward dysfunctions in adults and adolescents with depression was examined.•Coordinate-based, behavioral, network and molecular-genetic analyses were employed.•Both groups exhibited common activity decreases in the caudate and subgenual ACC.•Adults with depression specifically showed decreased reactivity in the putamen.•Adolescents showed decreased MCC and caudate but increased postcentral activity.